178 Angiotensin-(1–9) inhibits vascular smooth muscle cell proliferation and migration in vitro and neointimal formation in vivo. (6th June 2015) - McKinney, Clare A; Kennedy, Simon; Baillie, George; Milligan, Graeme; Nicklin, Stuart A
Abstract : Vascular smooth muscle cell (SMC) proliferation and migration underlie the pathogenesis of vein graft failure and in-stent restenosis. Current interventions inhibit both SMC and endothelial cell (EC) growth, leading to thrombosis and re-occlusion. Angiotensin II (AngII) is a key regulator of VSMC proliferation and migration. A counter-regulatory axis of the renin angiotensin system (RAS) has been identified which inhibits AngII and is centred around angiotensin converting enzyme2 and Ang-(1–7) acting at Mas. We recently reported Ang-(1–9) as a novel member of this axis, acting at the angiotensin type 2 receptor (AT2 R) to inhibit cardiac remodelling. Here we investigated the role of Ang-(1–9) in human SMC and EC migration and proliferation and vascular injury in vivo, and compared it to Ang-(1–7). SMC and EC were isolated from human saphenous veins. To assess migration, EC and SMC were stimulated with Ang II and Ang-(1–9) or Ang-(1–7) +/- the AT1 R, AT2 R or Mas antagonists losartan, PD123, 319 (PD) or A779, respectively, and a wound healing assay performed. To assess proliferation, EC and SMC were stimulated with fetal calf serum (FCS) and Ang-(1–9) or Ang-(1–7) ± losartan, PD or A779. Proliferation was assessed using MTS and Edu assays. An in vivo mouse model was established via wire injury to the carotid artery. Ang-(1–7) or Ang-(1–9) ± PD or A779 were delivered subcutaneously via minipumps and neointima (NI) formation quantified 28 days post injury. Ang-(1–9) and Ang-(1–7) inhibited Ang II induced VSMC migration (Ang II 98.9 ± 1.1%, Ang-(1–9) 43.3 ± 3.3% and Ang-(1–7) 41.8 ± 4.6% wound closure; P < 0.001 vs Ang II). Furthermore, both peptides significantly inhibited FCS induced VSMC proliferation (P < 0.05). The inhibitory effects of Ang-(1–9) and Ang-(1–7) on VSMC migration and proliferation were selectively blocked by PD and A779, respectively, suggesting Ang-(1–9) acts via the AT2 R and Ang-(1–7) via Mas. Neither Ang-(1–9) or Ang-(1–7) prevented EC migration or proliferation. In vivo wire injury of the mouse carotid artery induced significant NI formation at 28days (NI/media area (NI/MA) 0.80 ± 0.07 injured control vs 0.01 ± 0.01 sham; P < 0.001); this was attenuated by Ang-(1–9) (NI/MA 0.17 ± 0.1; P < 0.001 vs injured control) and Ang-(1–7) (NI/MA 0.40 ± 0.07; P < 0.05 vs injured control). The effects of Ang-(1–9) were blocked by PD (P < 0.001 vs Ang-(1–9) alone) while the effects of Ang-(1–7) were blocked by A779 (P < 0.05 vs Ang-(1–7) alone), suggesting that in vivo Ang-(1–9) acts via the AT2 R and Ang-(1–7) acts via Mas. We demonstrate for a novel, direct effect of Ang-(1–9) in inhibiting VSMC proliferation and migration in vitro, and reducing neointimal formation in vivo via the AT2 R. These data provide further insight into the role of the Ang-(1–9)/AT2 R interaction in the vasculature and highlights the potential of Ang-(1–9) as a therapeutic agent for vascular remodelling.